The Effect of NAA and Ga3on The Growth Performance of Ceriops tagal Seedling - Rini Budihastuti; Erma Prihastanti; Yulita Nurchayati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Plant Growth Regulator (PGR) had been widely utilized in improving plant quality and productivity. The mechanism includes the manipulation of plant adaptibility over environmental stress. This research aimed to study the efect of PGR on the growth of C. tagal seedling and to formulate the applicable treatment to improve its growth performance. The research was conducted through laboratory experiment, including tthe combination of NAA and GA3 with the designed concentration of 0 ppm, 150 ppm and 300 ppm. The experiment lasted for one month and involved weekly observation. The plants were treated by spraying once every three days. Observations were conducted to the survival rate, height increment and leaf number development. ANOVA was conducted as statistical analysis method. The result showed that there were no significant effect of PGRs on the height increment of C. tagal seedling. The survival rate was lowest in the control and 150 ppm NAA treatments, while treatment with 300 ppm GA3was highest. The application of 300 ppm GA3was the best treatment for the livelihood of C. tagal seedling, while the application of 150 ppm GA3 was considerable alternative due to its growth performance. This research provide a novel finding concerning the application of PGRs on the seeding process of C. tagal. Thus, it could be applied in the seeding activities by the mangrove farmers to improve the productivity and quality of mangrove seedling.